Synthesis and catalytic properties of metal nanoparticles: Size, shape, support, composition, and oxidation state effects - Cuenya, Beatriz Roldan (Thin solid films, 2010)
Exciting new opportunities are emerging in the field of catalysis based on nanotechnology approaches. A new understanding and mastery of catalysis could have broad societal impacts, since about 80% of the processes in the chemical industry depend on catalysts to work efficiently. Efforts in surface science have led to the discovery of new heterogeneous catalysts, however, until recently the only way to develop new or improved catalysts was by empirical testing in trial-and-error experiments. This time-consuming and costly procedure is now rapidly being replaced by rational design methods that utilize fundamental knowledge of catalysts at the nanoscale. The advent of nanoscience and nanotechnology is providing the ability to create controlled structures and geometries to investigate and optimize a broad range of catalytic processes. As a result, researchers are obtaining fundamental insight into key features that influence the activity, selectivity, and lifetime of nanocatalysts. This review article examines several new findings as well as current challenges in the field of nanoparticle based catalysis, including the role played by the particle structure and morphology (size and shape), its chemical composition and oxidation state, and the effect of the cluster support.